2021
DOI: 10.3389/fmed.2021.754490
|View full text |Cite
|
Sign up to set email alerts
|

The apoM/S1P Complex—A Mediator in Kidney Biology and Disease?

Abstract: Kidney disease affects more than 10% of the population, can be both acute and chronic, and is linked to other diseases such as cardiovascular disease, diabetes, and sepsis. Despite the detrimental consequences for patients, no good treatment options directly targeting the kidney are available. Thus, a better understanding of the pathology and new treatment modalities are required. Accumulating evidence suggests that the apolipoprotein M/sphingosine−1-phosphate (apoM/S1P) axis is a likely drug target, but signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“…Our human and mouse data suggest the possibility that the endothelial and lymphopoietic defects observed in the total-body Apom –/– mice may not occur in response to a partial reduction of HDL-S1P in humans or mice. Emerging evidence points to potentially important roles of HDL-ApoM-S1P in heart failure and kidney disease ( 61 , 68 ), and it will be of interest to examine whether this complex links insulin action to those pathologies. Further studies on the effects of ApoM-S1P will be of great relevance to understanding this evolutionarily conserved complex and its effects on insulin resistance and its vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our human and mouse data suggest the possibility that the endothelial and lymphopoietic defects observed in the total-body Apom –/– mice may not occur in response to a partial reduction of HDL-S1P in humans or mice. Emerging evidence points to potentially important roles of HDL-ApoM-S1P in heart failure and kidney disease ( 61 , 68 ), and it will be of interest to examine whether this complex links insulin action to those pathologies. Further studies on the effects of ApoM-S1P will be of great relevance to understanding this evolutionarily conserved complex and its effects on insulin resistance and its vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…ApoM is suggested to modulate HDL metabolism and exhibit anti-atherosclerotic functions. HDL-ApoM-S1P complex activates signaling cascades that maintain vascular integrity and decrease inflammatory reactions ( Christoffersen et al., 2011 ) and recent reports have described the role of ApoM in triglyceride turnover and renal diseases ( Bisgaard and Christoffersen, 2021 ). ApoM has one N- glycosylation site at Asn-135.…”
Section: Glycans On Apolipoproteins and Their Biological Rolementioning
confidence: 99%
“…ApoM is a small apolipoprotein of 26 kDa, which is highly produced in the liver and kidneys [ 198 , 199 ]; 95% of plasma apoM is associated with HDL, and 5% of plasma apoM is present in LDL, VLDL and chylomicron particles in humans and other animals [ 200 ]. ApoM has been reported to bind megalin and to be strongly expressed in kidney proximal tubular cells [ 201 ].…”
Section: Roles and Biological And Pathological Functions Of Apolipopr...mentioning
confidence: 99%
“…However, Brinck et al reported elevated S1P and diminished apoM in HDL particles in patients with CKD [ 205 ]. Uremia increases plasma apoM by 25% but has no effect on S1P [ 198 ]. Svarrer et al reported that urinary apoM serves as a biomarker of acute kidney injury in young children after heart surgery [ 206 ].…”
Section: Roles and Biological And Pathological Functions Of Apolipopr...mentioning
confidence: 99%
See 1 more Smart Citation